Comprehensive Preformulation, Formulation, and Stability Evaluation of Curcumin Nanoemulsion for Enhanced Bioavailability - Smita Srivastava; Dr. Harinth Dwivedi; Dr. Rajiv Gupta (The Bioscan, 2026)
Background: Curcumin, a polyphenolic compound from Curcuma longa, exhibits potent therapeutic effects but suffers from poor aqueous solubility, instability, and low oral bioavailability.1,9,5 Methods: A curcumin nanoemulsion was optimized using a Quality by Design (QbD) approach with Box–Behnken design. Thirteen formulations were prepared by high-shear homogenization and ultrasonication, and evaluated for globule size, PDI, zeta potential, viscosity, pH, refractive index, and in vitro drug release.2,5,10